2014
DOI: 10.1387/revpsicodidact.10876
|View full text |Cite
|
Sign up to set email alerts
|

Parental Socialization Styles and Psychological Adjustment. A Study in Spanish Adolescents // Los estilos parentales de socialización y el ajuste psicológico. Un estudio con adolescentes españoles

Abstract: ResumenContribuyendo al actual debate de la literatura acerca del estilo educativo parental óptimo para el mejor ajuste psicosocial de los hijos, el objetivo de este estudio fue analizar qué estilo se relaciona con el mejor ajuste psicológico de los adolescentes españoles. Participaron en el estudio 772 adolescentes, 358 hombres (46.4%) y 414 mujeres (53.6%), entre 12 y 17 años (M = 14.95, DT = 1.59). Se clasificó a las familias según su estilo de actuación (autorizativo, indulgente, autoritario o negligente).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 54 publications
9
43
1
17
Order By: Relevance
“…The positive influence that the family can have on their children's learning processes, motivation and school performance has been shown in numerous studies (Blanch, Durán, Valdebenito, & Flores, 2013;Fuentes, García, Gracia, & Alarcón, 2015;Villi ger, Wandeler, & Niggli, 2014). This influence is associated with the practice of certain measures that favor a positive environment and adaptation in the home.…”
Section: Introductionmentioning
confidence: 93%
“…The positive influence that the family can have on their children's learning processes, motivation and school performance has been shown in numerous studies (Blanch, Durán, Valdebenito, & Flores, 2013;Fuentes, García, Gracia, & Alarcón, 2015;Villi ger, Wandeler, & Niggli, 2014). This influence is associated with the practice of certain measures that favor a positive environment and adaptation in the home.…”
Section: Introductionmentioning
confidence: 93%
“…Según refieren en su estudio Cerezo, Casanova, de la Torre y , los alumnos con padres considerados tanto permisivos como democráticos utilizan en mayor medida estrategias de aprendizaje autorregulado, incidiendo esto positivamente en el desempeño académico de los alumnos. En estudios recientes realizados en España el estilo parental considerado más idóneo resultó ser el permisivo ( Fuentes, García, Gracia & Alarcón, 2015;Pérez Alonso-Geta, 2012). Asimismo en Portugal, un estudio refiere que los adolescentes de familias indulgentes puntuaron igual o mejor que los de familias democráticas en ajuste psicosocial ( Rodrigues, Veiga, Fuentes & García, 2013).…”
Section: Estilo Permisivounclassified
“…The weak connection between amount of help and achievement widened the explanatory search to variables such as quality of interaction and style of family involvement (Fuentes, García, Gracia, & Alarcón, 2014;García-Linares, de la Torre, Villa Carpio, Cerezo, & Casanova, 2014). Cooper, Lindsay, and Nye (2000) found that children of families which encourage autonomy with homework demonstrate better rates of completion and results than children of more interventionist families.…”
Section: Family Involvementmentioning
confidence: 99%